2010
DOI: 10.1007/s12032-010-9699-5
|View full text |Cite
|
Sign up to set email alerts
|

MUC2 and MUC6 apomucins expression in human gastric neoplasm: an immunohistochemical analysis

Abstract: Apomucins play important biological roles in cell-cell and cell-extracellular matrix interactions, in cell signaling, and in biological properties of cancer cells. Their specific pattern of expression during the different steps of tumor progression toward adenocarcinoma suggests that they play significant roles in tumorigenesis. The family of secreted mucins, gel-forming components of viscoelastic mucus gels protecting the epithelia, includes mucins MUC2 and MUC6. Their principle function is to contribute in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The MUC2 is secreted onto mucosal surfaces, where it is secreted from goblet cells in the epithelial lining into the lumen of the stomach [34]. As reported, MUC2 was high expression in gastric cancer [35]. Although uc001lsz seems playing as tumor suppressor gene in gastric cancer and many other types of tumors, it may play different role in prostate cancer where uc001lsz was highly expressed (Figure 3C).…”
Section: Discussionmentioning
confidence: 81%
“…The MUC2 is secreted onto mucosal surfaces, where it is secreted from goblet cells in the epithelial lining into the lumen of the stomach [34]. As reported, MUC2 was high expression in gastric cancer [35]. Although uc001lsz seems playing as tumor suppressor gene in gastric cancer and many other types of tumors, it may play different role in prostate cancer where uc001lsz was highly expressed (Figure 3C).…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, MUB 70 is not toxic for living cells as it has no cell penetration property, allowing its specific localization in the mucus layer located on the epithelium surface. In addition to the colonic mucinous carcinoma (30), Muc2 expression is up-regulated in mucinous carcinomas affecting various organs (31), including the lung (32), the stomach (33,34), the breast (35), the prostate (36), and the bile ducts (37). Hence, targeting Muc2 with MUB 70 , as observed on human colonic mucinous carcinomas, is anticipated to provide promising innovative approaches to develop new prognosis and diagnostic tools on various mucinous carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…In the process from superficial gastritis to atrophic gastritis and finally to the formation of GC, the positive level of PGC continues to decline, which indicates that the in situ expression of PGC may have a negative correlation with the formation of GC [ 46 ]. And the results showed that the expression of MUC6 was decreased in GC tissues, but surprisingly, there was no significant difference between the expression of MUC6 in GC tissues and the gender, tumor site, lymphatic infiltration, clinical stage, metastasis, Lauren intestinal type, diffuse type, and mixed type GC tissues [ 47 ].…”
Section: Discussionmentioning
confidence: 99%